Furocoumarins: A review of biochemical activities, dietary sources and intake, and potential health risks. (March 2018) - Melough, Melissa M.; Cho, Eunyoung; Chun, Ock K.
Highlights: Furocoumarins are photoactive compounds occurring naturally in numerous plant species. Furocoumarins can form DNA crosslinks when photoactivated, thereby disrupting DNA replication. Phototherapy using furocoumarins with UVA have been associated with increased skin cancer risk. Estimates of the level of exposure to dietary furocoumarins are highly variable. Potential risks associated with dietary furocoumarin exposure have not been fully clarified.